Situs Inversus Totalis on 18F-FDG PET/CT: A Case Report and a Literature Review - Liu, Xu-Sheng; Wu, Rui-Min; Wan, Hua-Bing; Chen, Yi-Jia; Tan, Fan; Zeng, Dao-Bing; Yang, Yi; Pei, Zhi-Jun (Frontiers in Medicine, 2022)
A 62-year-old female patient with pathologically confirmed left lung small cell neuroendocrine carcinoma. The patient was referred to our positron emission tomography (PET)/CT center to look for possible metastatic diseases. After fasting for 8 h, the fasting blood glucose level of the patient was 7.1 mmol/L. The patient was intravenously injected with a 6.42 mCi (238 MBq) 18F-fluorodeoxyglucose (FDG) imaging agent. After the patient rested for 1 h, we scanned the patient with SIEMENS Biograph mCT 64 PET/CT camera. In addition to lung tumors and lymph node diseases, abnormal tracer uptake in the patient's thyroid was also found. PET/CT also showed situs inversus totalis of the patient, including the dextrocardia, liver on the left side, stomach, and spleen on the right side of the patient's body. The identification of anatomical variations and abnormalities by PET/CT imaging is very important to develop the best treatment for lung cancer.